An analysis of the presence of disciplines focused on radiation protection in the syllabus of technologist in radiology courses according to Standard 7.01 - STEPHANIE NELASCO DA SILVA; TATIANE ALMEIDA; Fernando Barcellos Razuck (Brazilian Journal of Radiation Sciences, 2022)
Undergraduate courses in technology were recognized in Brazil from the 1990s onwards, such as Technologist in Radiology (TR). According to the Ministry of Education (MEC), the TR carries out activities in Radiotherapy, Radiology and Nuclear Medicine, for example, in addition to coordinating and supervising teams in radiation protection. It is then verified that, in some areas of TR performance, prior knowledge regarding radiation protection (RP) is necessary. In this sense, the objective of this work is to analyze the syllabus of higher education institutions that offer the TR course in Brazil and to verify the disciplines that address knowledge related to RP, according to Standard 7.01 (Certification of Qualification for acting as Radiation Protection Supervisor). The disciplines in question are Shielding Calculation, Dosimetry, Statistics, Radiation Physics, Fundamentals of Basic Physics, Waste Management and Transport, Nuclear Instrumentation, Legislation and Standardization, Nuclear Medicine, Radiobiology and Radiation Protection. To this end, a documentary research was carried out on the syllabus found in all educational institutions in the country that offer the TR course and the presence of disciplines related to RP was analyzed. It is observed that the offer of disciplines varies from region to region, which can also occur intraregionally, so that there is a need to offer disciplines related to RP to adapt to the 7.01 standard. It is intended, with this study, to contribute to the debate about the syllabus profile on RP of TR courses in view of the importance of this theme in their professional activity.